Structure of nucleosome-bound human PBAF complex - Li Wang; Jiali Yu; Zishuo Yu; Qianmin Wang; Wanjun Li; Yulei Ren; Zhenguo Chen; Shuang He; Yanhui Xu (Nature Communications, 2022)
BAF and PBAF are SWI/SNF family chromatin remodeling complexes that create nucleosome-depleted regions for transcription activation. Here the authors report the structure of a 13-subunit human PBAF in complex with acetylated nucleosome in ADP-BeF3-bound state that provides structural insights into PBAF-mediated nucleosome association.